The Sasak Pepaosan Tradition as a Medium of Communication with God - Raudloh, St.; Fahrurrozi, Fahrurrozi; Shubhi, Muhammad; Bahri, Syaiful; Husnan, Lalu Erwan (Ulumuna, 2024)
One local tradition of the Sasak people that has been maintained is conerned with pepaosan. This study explores the meaning of symbols and cultural values in the pepaosan tradition amongst the Sasak in West Lombok, West Nusa Tenggara, in eastern Indonesia. It employed ethnography with a phenomenological approach. All data were collected through observation, interviews, and documentation. These data were further analyzed qualitatively in four steps: domain analysis, taxonomic analysis, component analysis, and determining themes. This study argues that pepaosan tradition and other instruments serve as a communication medium and a symbol of cultural values, expressing gratitude for all the gifts God has bestowed. It also denotes a request to God to grant the wishes of the Sasak people. The symbols also embody the value of hope and advice for the Sasak people to live a good life, aligning with ancestral teachings and religious guidance.